Mode of delivery affects the bacterial community in the newborn gut - Biasucci, Giacomo; Rubini, Monica; Riboni, Sara; Morelli, Lorenzo; Bessi, Elena; Retetangos, Cristiana (Early human development, 2010)
The first colonisation of the intestine is one of the most profound immunological exposures faced by the newborn and it is influenced by external and internal factors. The early composition of human microbiota could have long-lasting metabolic effects and the initial composition of human intestinal bacteria is also known to affect postnatal immune system development, as we are already aware that reduced microbial stimulation during infancy would result in slower postnatal maturation of the immune system and development of an optimal balance between TH1 and TH2-like immunity. Mode of delivery has a major role on the composition of intestinal microbiota in early infancy, as it has been shown that infants born by Caesarean section (CS) have lower numbers of Bifidobacteria and Bacteroides compared with vaginally born infants. We designed a study to investigate the influence of mode of delivery (CS vs. vaginal delivery) on intestinal microbial composition on day 3 of life using PCR-denaturing gradient gel electrophoresis (DGGE) and PCR-temperature gradient gel electrophoresis (TGGE). Both DGGE and TGGE analyses have been used, together with the specific amplifications for 10 Bifidobacterium sp., 3 Ruminococcus sp., and Bacteroides that all have a highly relevant physiological role in the intestinal ecosystem of the newborn. A total of 46 term infants were enrolled in the study, consecutively recruiting all the CS-delivered babies (n = 23; 8 males and 15 females) and the immediately following spontaneously delivered babies (n = 23; 11 males and 12 females). DGGE analysis carried out with Bifidobacterium-specific primers revealed the presence of this genus in 13 of 23 (56.5%) samples derived from vaginally delivered newborns but in none of the samples obtained from newborns delivered by CS. PCR analysis with Bifidobacterium-species-specific primers showed that naturally delivered infants had a large number of bifidobacterial species, whereas in CS-delivered babies only two samples (8.7%) gave positive results, one for B. longum and another for B. gallicum. In all babies enrolled, micro-organisms belonging to Ruminococcus species were absent and Bacteroides was found in 8.7% of spontaneously delivered babies only. Based on our findings, it seems that newborn's intestinal bacteria during the first 3 days of life are strongly influenced by mode of delivery. The intestinal flora of CS and vaginally delivered infants appears to be very different; the former being altered and characterised by a substantial absence of Bifidobacteria sp., the latter characterised by subject-specific microbial profiles, although predominant groups such as B. longum and B. catenulatum could be identified. In summary, mode of delivery does affect the early stage of intestinal bacterial colonisation, which is altered in CS-delivered infants compared with vaginally delivered infants, with only a minor influence of the type of feeding. In addition, the importance of methodological aspects for determining intestinal microbiota in clinical trials requires emphasis if intestinal microbiota composition is to be considered a measure of postnatal adaptation.